Rationing and screening in crowdinvesting-markets - Oliver Mäschle; Wilfried Dalvai (Universität Rostock, Institut für Volkswirtschaftslehre, 2016)
The allocation of shares on crowd-investing-platforms is best described by the phrase "first come, first served". An entrepreneur who sells corporate equity to a "crowd" of investors on such a platform chooses a fixed investment target before the investment period begins. Once the aggregate investments equal the investment target the financing period ends immediately. We demonstrate that this preferential treatment of early investors is not optimal because it potentially excludes informational disadvantaged investors and entrepreneurs from the market. We recommend a market design that allows for some excessive demand. Such a design would increase the willingness of informational disadvantaged investors and entrepreneurs to participate in the market. At the same time, it would minimize a platforms screening costs and maximize its profits.
Keywords: D40; D45; G21; G32; L10; 330; crowd-investing; initial public offering; excessive demand; market microstructure; asymmetric information